134k views
5 votes
Which sentence explains the correct first step in the solution of this equation?

4(X-3)=9
A.Add 2 to both sides.
B.Apply the distributive property to get 4x - 3 = 9.
C.Apply the distributive property to get 4x - 12 = 9.
D.Subtract 9 from both sides.​

User Danba
by
4.9k points

2 Answers

4 votes
Answer is C 4x-12=9 i think
User Zettt
by
5.1k points
5 votes

Answer:

C. Apply the distributive property to get 4x-12=9.

Explanation:

To get x out of the parentheses, you have to use the distributive property by multiplying both x and -3.

Hope this helps you :)

User Neurozero
by
5.1k points